Charting the digital route to net-zero: A framework for sustainable industry practices - Juan Carlos Monroy-Osorio (Cleaner Logistics and Supply Chain)
This study investigates the application of a comprehensive framework for implementing digital strategies towards achieving net-zero emissions in Spanish manufacturing firms. It explores the adoption of digitally enabled and digital-first strategies in 354 medium-sized companies, utilizing Internet of Things (IoT) and Artificial Intelligence (AI) technologies to augment and reinvent environmental management practices. Digitally enabled strategies are found to be prevalent, optimizing existing processes through IoT for resource conservation and predictive maintenance. A modest yet growing number of firms adopt digital-first strategies, integrating AI to create innovative pathways for energy use optimization and waste reduction. However, a subset of firms remains reliant on traditional methods, indicating significant potential for digital integration. The paper highlights the strategic importance of digital tools in enhancing operational efficiencies and developing new, inherently sustainable business models. It emphasizes the need for an integrated approach that combines the strengths of digital innovation with traditional management to drive the industry towards a sustainable and net-zero future. The framework provides a nuanced classification of digital strategies and their contribution to net-zero objectives, offering insights into the effectiveness of these practices across various industrial sectors.